Lower back and lower limb injury in ballet dancers: Incidence and implications - Battisti, J. (The College at Brockport, State University of New York, 2011)
While ballet looks graceful and soft, there is a real threat of injury to the ballet dancer. This senior honors thesis looks at common injuries suffered by the dancers, their cause, and ways to avoid them. The first danger explained is over-exerting children. Children have growing bodies, with underdeveloped bones and muscles. Because of this, they should not be expected to perform certain movements that adult ballet dancers are capable of. Often child dancers will attempt unmodified techniques that are unsafe for people at their developmental level.